Long-and short-range structure of SnO2 nanoparticles: Synthesis and photo(electro)catalytic activity - da Silva, Gelson T.S.T.; Lopes, Osmando F.; Catto, Ariadne C.; Patrocinio, Antonio Otavio T.; Rodrigues, João E.F.S.; Mesquita, Alexandre [UNESP]; Ribeiro, Caue; Avansi, Waldir; da Silva, Luís F. (Elsevier, 2023)
We report herein a detailed study on the influence of hydrothermal treatment temperature on both long- and short-range structures of SnO2 nanoparticles (NPs) applied as photocatalysts for the discoloration of organic pollutants and as photoanodes for water splitting. Synchrotron X-ray diffraction and X-ray absorption near-edge spectroscopy measurements confirmed the enhancement of the structural order of SnO2 NPs as a function of hydrothermal temperature. Fourier transform infrared spectroscopy revealed that the hydrothermal treatment increased the amount of hydroxyl groups on the SnO2 NPs surface. Regarding the photocatalytic activity, the NPs were able to promote the discoloration of different dyes that can act as potential organic pollutants. The photoelectrocatalytic performance of the samples depended on the hydrothermal treatment temperature, with the degree of crystallinity and surface hydroxyl groups playing a significant role in their performance as photoanodes. In particular, the NPs treated at a higher temperature presented a better degree of crystallinity, in addition to many hydroxyls on their surface, leading to increased mobility of the photogenerated charge carriers and improving the interaction between the molecules degraded and the material surface. The results demonstrated that the hydroxyls adsorbed on the SnO2 surface favor the formation of hydroxyl radicals, a species that indirectly participate in the photocatalytic oxidation of rhodamine B dye. The photoelectrocatalytic tests showed that the NPs treated at 200 °C increased oxygen evolution reaction performance.
Keywords: Nanoparticles; Photoelectrocalysis; Synchrotron XRD; Tin dioxide; Water splitting; Water treatment; XANES